Clinical evaluation and management of a 45-year-old man with confusion, psychosis, agitation, stereotyped behavior, and impaired speech - Xiaolin Deng; Paulo J. Negro; Patrick L. Jung; Christopher M. Marano; Stephanie Knight; Seshagiri R. Doddi; Nana Y. A. Nimo; Rachel M. LeMalefant; Drew A. Myers; Andrea K. Haake; Rebecca Chandler (Case Reports in Psychiatry)
Our patient Mr. A is a mentally and physically disabled gentleman. He was first diagnosed with bipolar disorder as a teenager. He incurred a lumbar spinal injury due to a motor vehicle incident in his 20s which led to weakness, numbness, and frequent infection over both of his lower extremities. He also developed alcohol addiction over the course of his life. Mr. A presented to our facility with complicated neuropsychiatric symptoms. By adopting various clinical strategies, we were able to control his symptoms of agitation, self-harm, mood swings, and stereotyped behavior. However, we were not able to improve his neurocognitive functioning or speech impairment which seemed to become severe and irreversible in a period of a few months. We felt disappointed and perplexed by the mixed treatment responses. To understand Mr. A’s clinical presentation, various laboratory tests and imaging studies were performed. Different psychotropic medications were used to manage his symptoms. Gradually, we felt that we were able to understand this case better clinically and etiologically. His bipolar disorder, alcohol addiction, and physical injury had likely all contributed to his neuropsychiatric symptoms, directly or indirectly. It is highly possible that an alcohol-related progressive dementia along with his chronic bipolar disorder played a key role in the progression of his brain neurodegeneration. Also, Wernicke-Korsakoff syndrome could reasonably be considered having developed during his clinical course. Moreover, the fluctuation of the patient’s neuropsychiatric symptoms we observed during his hospitalization reflects the increased vulnerability of the human brain under sustained neurodegeneration.